Public Sector Criminological Research: The Australian Institute of Criminology, 1972–2022 - Smith, Russell G. (Palgrave Macmillan, 2023)
This book explores the role and development of criminological research in the public sector during the last half-century. It identifies the benefits such research has provided and assesses whether the community has received value for the funds expended. The Australian Institute of Criminology is used as a case study to illustrate the challenges and pressures facing those who have sought to carry out independent crime and justice research in the public sector, to assess what fifty years of work has achieved and to determine whether or not there remains a need for criminologists to be employed by governments. The book is based on extensive archival research, administrative data analysis, interviews with current and previous staff and the perspectives of scholars in comparable institutions globally. It presents new historical information as well as current and future critical perspectives on crime and justice research in a unique Australian government organization. Russell G Smith has qualifications in law, psychology and criminology from the University of Melbourne, Australia, and a PhD from King’s College London, UK. After almost 25 years working at the Australian Institute of Criminology, he is now Honorary Fellow at the Institute and Professor in the College of Business, Government and Law at Flinders University, Australia.